Analisis Kejenuhan Kerja Perawat High Care Unit (HCU) - Marwansyah Marwansyah; Adi Isworo; Wahyudi Wahyudi (Prodi Keperawatan Purwokerto, 2021)
Background: Burnout experienced by many social workers, especially nurses. Nurses in the HCU have patients with critical conditions and are fully dependent. This may impact on the decrease in the quality of care by nurse HCU. This study aims to determine the factors associated with burnout in HCU nurses. These factors include internal factors (age, gender, length of service, marital status, education level and personality factors) and external factors (management factors, professional factors and social factors).Method: This research uses analytical research design with a Cross Sectional approach. The sample of this research is all nurse HCU had 80 respondents. Data collection was conducted on 17 June to 30 July 2017 using Maslach Burnout Inventory (MBI), Work Locus of Control (WLCS) and for eksternal factor questionnaire research instrument. Data analysis was univariate analysis, bivariate using chi square and multivariate.The results: showed most (53,8%) of HCU nurses had high burnout. There is a significant relationship between personality factors, management factors and social factors premises burnout. there is no significant relationship between age factor, sex, work period, marital status, education level and professional factor.Conclusion: The dominant factor in this research is social factors where HCU nurses with social factor problems are more likely to experience high burnout. Hospital management provides efforts to provide personal counseling and peer sharing activities, provide socialization about nurse’s legal protection at work and rewarding nurses.